2014
DOI: 10.1111/ejss.12199
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Scottish topsoil organic matter content from colour and environmental factors

Abstract: Summary Assessment of soil organic matter content using laboratory analysis can be costly and time consuming, so limiting how often land managers assess this important property. This work demonstrates an ability to estimate topsoil organic matter content from field observations alone and provides a method by which rapid and cost‐effective assessments of soil organic matter status may be made. Models using environmental factors from the National Soil Inventory of Scotland (NSIS) dataset as inputs to a neural ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Recently, there has been renewed interest in creation of soil test kits optimized for agronomical field use as a result of increasing access to technology such as portable sensors (Piikki et al., 2016). Key to this is the rising ubiquity of smartphones, which are being increasingly used in environmental management applications (Aitkenhead, Donnelly, Coull, & Hastings, 2014) and soil science (Aitkenhead et al., 2015; Delgado, Kowalski, & Tebbe, 2013; Stiglitz et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there has been renewed interest in creation of soil test kits optimized for agronomical field use as a result of increasing access to technology such as portable sensors (Piikki et al., 2016). Key to this is the rising ubiquity of smartphones, which are being increasingly used in environmental management applications (Aitkenhead, Donnelly, Coull, & Hastings, 2014) and soil science (Aitkenhead et al., 2015; Delgado, Kowalski, & Tebbe, 2013; Stiglitz et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Soil organic carbon and soil color has been demonstrated to be well correlated in several studies [11,12,30] and the optical sensor, used in this study, was designed specifically for mapping of TC content [17]. In this study, the best prediction model for TC was based on R, as measured with the optical sensor, and the contents of Sr and Zr, measured with the PXRF (i.e., no color variables).…”
Section: Discussionmentioning
confidence: 99%
“…Measurement in situ has potential to be cost- and labor-effective compared to laboratory analyses but it is a challenge to make accurate predictions under the non-standardized soil conditions prevailing on the farm (varying soil moisture and soil structure). A multitude of research studies has dealt with the issue of calibrating the often indirect field-based measurements against lab analyses to produce accurate values of a variety of soil properties [6]: electromagnetic conductivity (ECa) has been used widely to map spatial variation patterns of agricultural fields but also for prediction of specific soil properties, for example, cation exchange capacity (CEC), soil moisture content, soil organic carbon (SOC) content, and the fractions of clay, silt, and sand [7]; element concentrations measured with a portable X-ray fluorescence sensor (PXRF) in situ have been demonstrated to correlate with soil texture, SOC, and CEC [8,9,10]; Jung et al [11] showed that a multispectral camera can be used to predict SOC; and, recently, even the built-in cameras in mobile phones have been used as proximal soil sensors—Aitkenhead et al [12] predicted SOC from the registered values of soil color (red, green, and blue bands) registered with a mobile phone camera.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have been carried out to estimate soil variables through ANNs (Zhou et al ., 2008; Bocco et al ., 2010; Gago et al ., 2010; Parvizi et al ., 2010; Peng et al ., 2010; Ayoubi et al ., 2011; Mokhtari Karchegani et al ., 2011; Besalatpour et al ., 2013; Dai et al ., 2014; Aitkenhead et al ., 2015). Also, some studies have been conducted to predict crop yield by remote sensing, stochastic, ANN and simulation models (Bannayan and Crout, 1999; O'Neal et al ., 2002; Bartoszek, 2014; Farjam et al ., 2014; Domínguez et al ., 2015; Emamgholizadeh et al ., 2015; Dias and Sentelhas, 2017), based on weather, soil and growth characteristics as input data.…”
Section: Introductionmentioning
confidence: 99%